2021
DOI: 10.1002/pssr.202100086
|View full text |Cite
|
Sign up to set email alerts
|

On the Origin of Wake‐Up and Antiferroelectric‐Like Behavior in Ferroelectric Hafnium Oxide

Abstract: Research data are not shared.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
70
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 75 publications
(81 citation statements)
references
References 37 publications
11
70
0
Order By: Relevance
“…This is in stark contrast to commonly investigated capacitor structures, which have been reported to consist of disc-shaped grains with ⟨100⟩ out-of-plane textures [7][8][9]. Furthermore, the polarisation hysteresis behaviour ranged from ferroelectric to strongly asymmetric antiferroelectric (AFE)-like behaviour [4,6]. Additionally, it has been reported that the interface layer is changing in thickness and chemical composition during the dopant activation and crystallisation anneal of the ferroelectric [4,5].…”
Section: Introductionmentioning
confidence: 75%
See 3 more Smart Citations
“…This is in stark contrast to commonly investigated capacitor structures, which have been reported to consist of disc-shaped grains with ⟨100⟩ out-of-plane textures [7][8][9]. Furthermore, the polarisation hysteresis behaviour ranged from ferroelectric to strongly asymmetric antiferroelectric (AFE)-like behaviour [4,6]. Additionally, it has been reported that the interface layer is changing in thickness and chemical composition during the dopant activation and crystallisation anneal of the ferroelectric [4,5].…”
Section: Introductionmentioning
confidence: 75%
“…1c) behaves already ferroelectric at the beginning, the slope of the hysteresis becomes much steeper during wake-up, and can be therefore classified as non-split wake-up [6]. Samples annealed at lower temperatures on the other hand show an asymmetric wake-up [6]. Here, the pinching of the hysteresis is reduced with cycling, resulting in a more ferroelectric behaviour (see Fig.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…The first point can be explained by the asymmetric field distribution across the stack in the case of different interface layers surrounding the HZO. [48,49] For the targeted applications, the FE-TFTs must show FE plasticity (stable, partially switched polarization states) for programming at sub-coercive voltage conditions. The existence of these multi-state sub-loops has been directly observed for P-E measurements of MFM test structures (Figure 4b).…”
Section: Resultsmentioning
confidence: 99%